Proporcionalidade e precedentes obrigatórios - Oliveira, Luis Henrique Silva de (2022)
The current Brazilian procedural system has consolidated a double tendency in Brazilian law: that of granting binding effectiveness to judicial decisions and the codification of analytical and hermeneutical dogmatic theories of the interpretation of law and the basis of legal decisions. Although the importance of hermeneutical theories is recognized, the focus will be on the influence of analytical theories of law, due to the theoretical framework adopted. Legislative innovations are based on the search for increasing the rationality of legal discourse, however, they diverge in the sense of implementing this rationality. The theory of legal argumentation and the theory of principles, present in procedural codification, as a densification of the duty to justify legal decisions, seek correction as a synonym of procedural justice, through the logical and argumentative explanation of the premises used by judges in the context of discovery and the justification of judicial decisions. Mandatory precedents seek to rationalize the law through legal certainty, protection of the trust of jurisdiction, stability, unity, coherence of judicial decisions, as an expression of the demand for universalization and formal equality. There is a tension between justice and stability inherent to the coexistence of both procedural institutes. From this tension, the research problem is exposed, which consists in the investigation of a potential internal contradiction of the civil procedural codification when foreseeing both institutes and establishing correlations between them. It is shown that the research carried out adheres to the area of concentration of the Postgraduate Program in Procedural Law, as it deals with a method of judicial decision-making widely adopted in the jurisdiction of freedoms, namely, the maxim of proportionality, since the The program intends to study the process as a mechanism for promoting justice, the main objective of this method of resolving normative conflicts and mandatory precedents as an instrument for stabilizing the legal discourse. The purpose of the investigation was to find out whether the contradiction raised in the problem exists or not and, if so, under what conditions. The main theoretical contribution used for the research was Robert Alexy's theory of law, both the theory of principles and the theory of legal argumentation. It is concluded that the contradiction pointed out in the problem may exist, if associated with a form of understanding of the rules arising from mandatory precedents called improperly typifying.